The implementation of the problem-based learning model integrated with ethnoscience on students' critical thinking skills and learning motivation - Rifqy Kiara Cahyaningrum; Woro Sumarni; Suharto Linuwih (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2025)
Critical thinking skills and learning motivation exist in every student, but each individual possesses them at different levels. The aim of this study is to examine the correlation between the application of problem-based learning in science lessons—specifically on the topics of vibration, waves, and sound—and students' critical thinking skills and learning motivation. This research employed a one-shot case study design, which is a type of pre-experimental research. The sample consisted of 35 eighth-grade students from class VIII G at MTsN 1 Kota Serang. The sampling technique used was purposive sampling, and data were collected using tests. The result of the study indicate that: (1) based on the assessment of four aspects of students’ critical thinking skills, 27 students were categorized as very high and 8 students as high; (2) based on six aspects of learning motivation, 1 student was categorized as moderate, 22 students as high, and 12 students as very high; (3) the correlation between critical thinking skills and learning motivation through the ethnoscience-integrated problem-based learning model was 70.1%, with the calculated r-value exceeding the table r-value at a significance level of 0.05.The conclusion of this study is that students’ learning motivation and critical thinking skills through ethnoscience-integrated problem-based learning are strongly correlated.